THE RATIO OF N/K AND GRAIN YIELD OF LOWLAND RICE (Oryza sativa L.) AS AFFECTED BY DIFFERENT LEVELS OF NITROGEN APPLICATION AND IRRIGATION METHODS - Muhammad Kamal; M. S. Hadi; O. Ekasari; E. Setiawan (Universitas Lampung, 2013)
Lowland rice (Oryza sativa L.) still significantly contributes to Indonesian food security. Water shortage and the availability of N fertilizers frequently become major constraints in rice production, so efficient use of N fertilizers and water-saving irrigation are more preferable. The objective of the experiment was to evaluate the ratio of N/K and seed yield of lowland rice under different levels of nitrogen application and irrigation methods. The experiment was conducted in Gadingrejo-Pringsewu in 2011. The treatments were arranged in factorials with Split-Plot in Randomized Complete Block Design with three replications. Irrigation methods as main plots consisted of two levels, namely, conventional irrigation method (continous standing-water with 5 cm in depth) and irrigation method without flooding (continous saturated soil). Sub-plot was N fertilization consisting of four levels, that is, 150, 200, 250 and 300 kg Urea/ha. Lowland rice cv. Ciherang was planted in experimental plots of 4x5 m in size with row spacing of 25x25 cm. The result of the experiment indicated the ratio of N/K in rice leaves at 40 and 60 DAP, and at harvest time was not significantly affected by irrigation methods and N fertilization levels. The performance of yield components and rice production in conventional irrigation method and irrigation without flooding did not a significant diference although irrigation without flooding consumed less water. This means that irrigation without flooding could increase water use efficiency in lowland rice production. Key words: grain yield, lowland rice, ratio of N/K, yield components